التهاب الأنف التحسسي كعامل خطر في حدوث الربو القصبي - محمد, يسر; ابراهيم, مصطفى; اسماعيل, موسى (Latakia University Journal -Medical Sciences Series, 2019)
أجريت هذه الدراسة في قسم الأمراض الباطنة لمشفى الأسد الجامعي في اللاذقية خلال العام 2008-2009 ،وشملت 60 مريضا و مريضة يعانون من التهاب أنف تحسسي معزول، تم تقييمهم بفحص سريري كامل،وأجري لهم قياس وظائف التنفس(spirometry )بعد تصنيف التهاب الانف التحسسي حسب ARIA 2008 واعتمدنا معايير ERS لوظائف الرئة ،وسجلت النتائج كمايلي: · لم يلاحظ أي اضطراب في قيم ال spirometry عند مرضى التهاب الأنف التحسسي المتقطع سواءً كان خفيفاً أو متوسطاً إلى شديداً. · لوحظ عند مرضى التهاب الانف التحسسي المستمر مايلي : وجد اضطراب في قيمة FVC (<80%) عند حالتين فقط( 3.3%)، وجد اضطراب في قيمة FEV1 (<80%)عند 4 حالات فقط (6.7%)، وجد اضطراب في قيمة (%75-25) FEF (<65%) عند 21 حالة (35%). This study was carried out in the department of Internal Medicine at ALASSAD University Hospital in Lattakia during the year 2008-2009, and included 60 patients, with isolated allergic rhinitis were evaluated,clinical examination and spirometry were performed for all patients after classification of allergic rhinitis by ARIA 2008 classification. Predicted values for spirometry were those of European Respiratory Society (ERS) 2005,and results recorded: There is no abnormal value in spirometry for intermittent mild,moderate to severe allergic rhinitis. We observe in patients with persistent allergic rhinitis: (FVC<80%) in 2 patients (3.3%),(FEV1<80%) in 4 patients(6.7%),(FEF25-75%<65%) in 21 patients(35%).